Alix de Vergy et l’architecture religieuse en Bourgogne dans la première moitié du xiiie siècle - Sylvain Demarthe (Bulletin du Centre d’Études Médiévales d’Auxerre)
In the first half of the 13th century, the duchess Alix of Vergy plays an important political role by exercising the regency before her son Hugues IV comes of age around 1230. She’s also behind the construction or reconstruction of many important religious edifices, situated between Dijon and Beaune, which have never generated historical synthesis. Yet Alix of Vergy’s generous gifts favour the development of a transitional Burgundian architecture that is still attached to Romanesque traditions while opening to Gothic modernity. At the same time, those buildings also reflect the economic and demographic dynamism in progress since the 12th century, as well as some « flexibilities » of the authorities, in particular towards the inhabitants.